Evaluating the impact of green roof evapotranspiration on annual building energy performance. Issue 5 (9th April 2017) - Boafo, Fred Edmond; Kim, Jun-Tae; Kim, Jin-Hee
ABSTRACT: The performance of the building envelope predominantly determines the ultimate energy performance throughout the lifecycle of a building. A sustainable alternative to enhance roof performance while limiting heat flux through a roof is integrating passive techniques such as green roof. Particularly, green roof performance is sensitive to local climate. The main objective of this study was to evaluate the evapotranspiration effect of an extensive green roof on annual energy consumption of an office building in relation to the humid continental climate of Republic of Korea. The dynamic behavior of green roof and building energy performance were investigated through a parametric simulation method using green roof module in EnergyPlus coupled with jEPlus. Structural data of the reference building and ASHARE 90.1-2007 operational schedules were used as inputs for baseline building model while inputs for the green roof module were based on experimental data sets. Due to the influence of the humid conditions and local wind current on the evapotranspiration process, it was generally found that high leaf area index (LAI) reduced cooling energy demand and somewhat reduced heating energy demand as well; corresponding to the highest daily evapotranspiration fluxes of 4.79 mm day −1 in summer and 1.80 mm day −1 in winter. Increasing LAI from 20% to 100% cover increased evapotranspiration flux by 10.4% in summer and 80.2% in winter. Thus to minimize energy losses in winter, foliage cover must be carefully considered. Within limitations specified, the overall annual building energy consumption deceased by 90.9 GJ (3.7%).